Effect of cholesterol on the structure of membrane-attached cytochrome P450 3A4 - Navrátilová, Veronika; Paloncýová, Markéta; Kajšová, Michaela; Berka, Karel; Otyepka, Michal (Journal of chemical information and modeling, 2015)
Cholesterol is a widely researched component of biological membranes that significantly influences membrane properties. Human cytochrome P450 3A4 (CYP3A4) is an important drug-metabolizing enzyme, wherein the catalytic domain is attached to a membrane by an N-terminal α-helical transmembrane anchor. We analyzed the behavior of CYP3A4 immersed in a 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) membrane with various amounts of cholesterol. The presence of cholesterol caused ordering and thickening of the membrane and led to greater immersion and inclination of CYP3A4 toward the membrane. Cholesterol also lowered the flexibility of and tended to concentrate around membrane-immersed parts of CYP3A4. Further, the pattern of the CYP3A4 active-site access channels was altered in the presence of cholesterol. In summary, cholesterol in the membrane affected the positioning and structural features of CYP3A4, which in turn may have implications for the activity of this enzyme in various membranes and membrane parts with different cholesterol content.
Keywords: buněčná membrána; simulace molekulární dynamiky; Phosphatidylcholines; Protein Conformation; Cell Membrane; Humans; Cytochrome P-450 CYP3A; cytochrom P-450 CYP3A; katalytická doména; fosfatidylcholiny; Cholesterol; Molecular Dynamics Simulation; Catalytic Domain; lidé; konformace proteinů; cholesterol